PENGARUH KUALITAS LAYANAN TELEKOMUNIKASI TELKOMSEL TERHADAP KEPUASAN WISATAWAN DI KUTA - Nathania Sucahyo, Felicia; Sudiarta, I Nyoman; Darsana, I Wayan (Jurnal IPTA (Industri Perjalanan Wisata), 2025)
This study aims to determine the impact of the Telkomsel Tourist prepaid card on international tourists satisfaction in Kuta District. The data were processed using qualitative and quantitative analysis with Likert scale of 1-5. The quantitative data collection used purposive sampling by distributing questionnaires both online and offline to 100 respondents. This study utilized servqual indicators to assess the quality of Telkomsel Tourist prepaid card telecommunication services. The study examines the influence of reliability (X1), responsiveness (X2), assurance (X3), empathy (X4), and tangible aspects (X5) on tourist satisfaction (Y) for users of the Telkomsel Tourist prepaid card in Kuta District. The results indicate that reliability (X1), responsiveness (X2), and empathy (X4) have a significant partial effect on tourist satisfaction, while assurance (X3) and tangible aspects (X5) do not have a significant impact. Simultaneously, all variables X1, X2, X3, X4, and X5 significantly affect tourist satisfaction, with an F-value of 16.483, exceeding the F-table value of 2.311, and a significance level of 0.000. These findings suggest that improving service quality in terms of reliability, responsiveness, and empathy can enhance user satisfaction. Future research is recommended to include other variables, such as price impact, for a more comprehensive understanding of tourist satisfaction.